The surgical management of early-stage lung adenocarcinoma: is wedge resection effective? - Ji, Ying (J Thorac Dis, 2021)
BACKGROUND: The aim of the study was to explore the outcomes of wedge resection on patients with early-stage lung adenocarcinoma (LUAD) and further identify potential prognostic factors for these patients. METHODS: A retrospective cohort of 190 patients (99 solitary LUAD and 91 multifocal LUAD) undergone wedge resection from October 2014 to September 2015 was established. Cox proportional-hazards model was used to evaluate the significant clinical prognostic factors. Further, data on patients with multifocal adenocarcinoma after segmentectomy were retrieved and propensity score matching was used to compare the outcomes of patients with multiple pulmonary nodules (MPNs) after wedge resection and segmentectomy. RESULTS: The 5-year overall survival (OS), progression-free survival (PFS), and lung cancer speciﬁc survival of the 190 patients after wedge resection were 95.5%, 87.9%, and 97.7%, respectively. Multivariable analysis showed that MPN [hazard ratio (HR) 3.07; 95% confidence interval (CI), 1.05–8.98] and solid-dominant lesions (HR 15.87; 95% CI, 2.38–105.84) were independently associated with worse PFS. Further, propensity score matching analysis showed that MPN patients had better PFS after segmentectomy compared with wedge resection (94% vs. 80.9%, P=0.008). MPN patients were more likely to perform systematic mediastinal nodal sampling (95.6% vs. 59.3%, P<0.001) after segmentectomy compared to patients who underwent wedge resection. CONCLUSIONS: Wedge resection is a practical option for appropriately selected early-stage LUAD where tumor size is less than 2 cm and has a consolidation-to-tumor ratio ≤0.5. However, for MPNs, wedge resection may be not reliable and alternative procedures such as segmentectomy should be used.